2003
DOI: 10.1038/ncb1057
|View full text |Cite|
|
Sign up to set email alerts
|

EB1 reveals mobile microtubule nucleation sites in Arabidopsis

Abstract: In plants, it is unclear how dispersed cortical microtubules are nucleated, polarized and organized in the absence of centrosomes. In Arabidopsis thaliana cells, expression of a fusion between the microtubule-end-binding protein AtEB1a and green fluorescent protein (GFP) results in labelling of spindle poles, where minus ends gather. During interphase, AtEB1a-GFP labels the microtubule plus end as a comet, but also marks the minus end as a site from which microtubules can grow and shrink. These minus-end nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
249
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(272 citation statements)
references
References 30 publications
21
249
2
Order By: Relevance
“…Using an in vitro model that provides good access to the cortex combined with the hook decoration of MTs, Tian et al (2004) demonstrated that the MTs in the cortical array are predominantly oriented in a mixed polarity. This organization is in agreement with opposing growth directionalities of green fluorescent protein (GFP)-labeled MTs observed in the cortical array (Chan et al, 2003;Shaw et al, 2003). In contrast, Dixit et al (2006) reported that ϳ70% of CMTs have the same polarity and that this polar arrangement of CMTs occurs simultaneously with the coalignment of CMTs.…”
Section: Introductionsupporting
confidence: 64%
“…Using an in vitro model that provides good access to the cortex combined with the hook decoration of MTs, Tian et al (2004) demonstrated that the MTs in the cortical array are predominantly oriented in a mixed polarity. This organization is in agreement with opposing growth directionalities of green fluorescent protein (GFP)-labeled MTs observed in the cortical array (Chan et al, 2003;Shaw et al, 2003). In contrast, Dixit et al (2006) reported that ϳ70% of CMTs have the same polarity and that this polar arrangement of CMTs occurs simultaneously with the coalignment of CMTs.…”
Section: Introductionsupporting
confidence: 64%
“…Expression of AtEB1a:GFP has been reported to reveal the dynamic behavior of microtubules upon transgenic or transient expression in Arabidopsis, tobacco, and N. benthamiana cells (Chan et al, 2003;Mathur et al, 2003;Van Damme et al, 2004;Dixit et al, 2006;Brandner et al, 2008). However, transient coexpression of ABD2:GFP had no significant effect on microtubule polymerization (data not shown), indicating that microtubules are not affected by the inhibition of membrane movements induced by transient ABD2:GFP expression.…”
Section: Labeling Of Actin Filaments With Abd:gfpmentioning
confidence: 81%
“…To investigate whether ABD2:GFP expression may also affect microtubule dynamics, we expressed the Arabidopsis AtEB1a fused to GFP (AtEB1a:GFP; Chan et al, 2003). Expression of AtEB1a:GFP has been reported to reveal the dynamic behavior of microtubules upon transgenic or transient expression in Arabidopsis, tobacco, and N. benthamiana cells (Chan et al, 2003;Mathur et al, 2003;Van Damme et al, 2004;Dixit et al, 2006;Brandner et al, 2008).…”
Section: Labeling Of Actin Filaments With Abd:gfpmentioning
confidence: 99%
“…New MTs appear both in association with existing MTs and in areas devoid of MTs. Evidence for MT nucleation at cortical sites also comes from the observation that SPC98 (a component of the ␥-TuRC) and EB1 associate with newly formed MTs in the periphery of plant cells (Chan et al, 2003;Erhardt et al, 2002). MT polymerization sites marked by GFP-tagged EB1 associate with and dissociate from the cortex, which suggests that nucleating material constantly redistributes.…”
Section: Generation Of Noncentrosomal Mtsmentioning
confidence: 99%